KAJIAN YURIDIS TINDAK PIDANA PEMALSUAN MEREK DAGANG (Studi Kasus Putusan Pengadilan Negeri Yogyakarta Nomor : 354/Pid.Sus/2016/PN.Yyk) - SAIMAN, SAIMAN (Dinamika Hukum, 2018)
The background of the research is that the economic development of the globalization era, the level of civilization in society has evolved over time influenced by the culture of society. Culture is the result of work, taste and creativity. One of the works of human beings that influences the progress of humanity is Intellectual Property Rights, namely one of them. The right to the mark needs legal protection so that the creator gets legal protection. The purpose of this study was to: 1) Analyze the application of criminal law against criminal acts of trademark counterfeiting in the Yogyakarta District Court Decision Number: 354 / Pid.Sus / 2016 / PN.Yyk. 2) Analyzing the judge's legal considerations in making a decision on the crime of trademark counterfeiting in the Yogyakarta District Court Decision Number: 354 / Pid.Sus / 2016 / PN.Yyk. The method of approach in this writing is normative juridical. The specification of this study uses analytical descriptive. Data sources use secondary data. Data collection techniques use literature study and document study. To analyze the data, researchers used qualitative normative methods. Based on the results of the study it was concluded that: 1) The application of the law to the crime of trademark counterfeiting in the Yogyakarta District Court's decision Number: 354 / Pid.Sus / 2016 / PN. falsified, then it can be prosecuted and subject to criminal charges or the holding of an investigation. Without complaints from those who feel that they have been harmed by the fraud, there is no investigation from the police. Enforcement of complaints complained of in the Trademark Law, should be changed or returned to ordinary offenses, thus emphasizing the enforcement and protection of the law against consumers and causing a deterrent effect on perpetrators or counterfeiters of brands. 2) Judges' consideration in imposing a criminal offense against the perpetrator of brand fraud in the Yogyakarta District Court's decision Number: 354 / Pid.Sus / 2016 / PN. trial facts as well as things that alleviate and burden the defendant who are then judged as legal facts to become legal considerations. Other considerations about the crimes imposed are not for retaliation but prevention and coaching. The lack of attention is a consideration that relates to the impact of the defendant's actions, especially for the wider community. This consideration is important because it can affect the creative climate in working in the field of intellectual property rights and investment. Keywords: Counterfeit Crimes, Trademarks.